Current trends in the management of brachial plexus injuries - Bhandari, PS; Sadhotra, LP; Bhargava, P; Bath, AS; Mukherjee, MK; Babu, Pauline (Indian Journal of Neurotrauma, 2008)
In the last decade several advances have been added in the reconstruction of devastating brachial plexus injuries. This includes better understanding of the anatomy, advances in the imaging techniques, use of newer materials for nerve coaptation (e.g., fibrin glue), introduction of nerve conduits, incorporation of new immunosuppressive agents such as FK-506 and addition of new nerve transfers which selectively neurotize the target muscles close to the motor end plates. These new techniques have considerably improved the results of brachial plexus reconstruction, in particular, the upper plexal lesions.
Keywords: brachial plexus injuries; nerve repair; selective neurotization; nerve conduits; fibrin glue